Exploring global decolonising projects and English studies in the 21st century : a thematic analysis - Jamaluddin Aziz; Fuzirah Hashim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Decolonisation projects have proliferated with the increasing awareness of the hegemony that comes with globalisation. Decolonising English studies (both language and literature) is nothing new and often manifested at the implementation levels with the use of local literary texts and localised Englishes in the classroom. What collective voice has decolonising English studies achieved in relation to other decolonising projects, however, has not been fully scrutinised. The aim of this paper is to review past studies on some areas affected by the decolonising project and to try establishing its relationship to English studies itself. The overarching concern is expressed by these research questions: 1) What are some examples of decolonisation projects that can be found?; 2) What are the common themes of past studies on decolonisation projects?; And 3) How are these past studies contributing to the decolonisation of English studies? To achieve this, the review of literature is organised thematically to create links and synthesis. This paper adopts the definitions of decolonisation by Meera Ashar (2015) and Shahjahan et al. (2022). The thematic analysis reveals three main themes which are privileging indigenous knowledge, a re-evaluation of the curriculum, and the questioning of the epistemology of knowledge itself, with the first two themes bookending the last theme. We conclude that English studies should be coded as a tool of cultural-political literacy that is useful in helping us make sense of how inequalities are being reproduced via literary texts and the English language. This finding contributes toward an alternative understanding of the evolution in pedagogy and the innovative approaches in English studies so that its cultural imperialism is eliminated while providing a vanguard of possible retheorisation.